Association between inflammation and left ventricular thrombus formation following ST-elevation myocardial infarction. (3rd October 2022) - Holzknecht, M; Lechner, I; Reindl, M; Tiller, C; Fink, P; Mayr, A; Klug, G; Bauer, A; Reinstadler, S J; Metzler, B
Abstract: Background: Current evidence suggests a link between the inflammatory state and left ventricular thrombus (LVT) formation following ST-elevation myocardial infarction (STEMI). However, a comprehensive study investigating the association between inflammatory biomarkers and LVT diagnosed by cardiac magnetic resonance (CMR) is lacking. Purpose: The present study aimed to investigate the association of biochemical markers of inflammation with LVT as assessed by CMR imaging among patients with STEMI. Methods: We studied 309 patients with acute STEMI treated with primary percutaneous coronary intervention (pPCI) from the prospective MARINA-STEMI cohort study. Concentrations of high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), white blood cell count (WBCc), fibrinogen and D-dimer were measured two days after STEMI. Infarct characteristics and presence of LVT were assessed with the use of contrast-enhanced CMR at a median of 4 (interquartile range [IQR] 3–5) days after pPCI. Results: In total, 309 STEMI patients (18% female) with a median age of 57 (IQR 52–65) years were included. An LVT was observed in 8% (n=24) of the overall cohort and in 15% of patients with an anterior STEMI. Hs-CRP (OR: 2.16, 95% CI: 1.54–3.02, p<0.001), IL-6 (OR: 2.38, 95% CI: 1.48–3.81, p<0.001) and fibrinogen levels (OR: 2.05, 95% CI: 1.40–3.00, p<0.001) were significantly associated with presence of LVT. Among all assessed inflammatory biomarkers, only hs-CRP was independently associated with LVT after adjustment for markers of inflammation and CMR parameters (OR: 1.77, 95% CI: 1.21–2.59, p=0.004). Conclusion: In patients with STEMI treated with pPCI, inflammatory markers (hs-CRP, IL-6 and fibrinogen) are associated with the presence of LVT. However, only hs-CRP was independently associated with the occurrence of LVT, highlighting the key role of CRP as clinical risk marker for LVT formation in STEMI patients treated with pPCI. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Austrian Science Fund (FWF)Austrian Society of Cardiology